A precarious balance: consequences of Zimbabwe's fast-track land reform - Sarimana, Ashley (Rhodes University, Faculty of Humanities, Department of Sociology and Industrial Sociology, 2006)
This thesis is a detailed account of Zimbabwe's controversial fast-track land reform programme. Zimbabwe's land reform history has been discussed extensively, with a focus on land redistribution. The fast-track land reform programme transferred eleven million hectares of land from 4 000 white commercial farmers to 51 543 landless peasant families. The thesis begins by offering some land reform theories and gives an overview of the land question in Southern Africa. This is followed by a discussion of Zimbabwe's land question from a historical perspective. Next is a periodised account of the successes and failures of land reform attempts made by the Zimbabwean government from independence in 1980 to 1998 when the fast-track land reform programme was conceived. Zimbabwe's political and economic situation at this time is significant. The context for fast-track land reform includes a discussion about the national question in Zimbabwe and the deteriorating status of white citizenship; the rise of Zimbabwe's liberation war veterans as a formidable force and the formation of the Movement for Democratic Change as a strong political party that was challenging, among others, the dominance of the ruling Zanu-PF party and its policies. The blueprint for fast-track land reform is discussed in order to contrast it to how the reform unfolded in practice. In this regard, the response of the international community to the violence and lawlessness that characterised fast-track land reform is worth mentioning, especially since it has bearing on how Zimbabweans are trying to cope with life in a radically altered physical and social environment, following the land reform exercise. The consequences of fast-track land reform are analysed in terms of development and the plight of Zimbabwe's farm workers; the internal displacement of hundreds of thousands of farm workers, white commercial farmers and others in Zimbabwe's countryside and whether or not fast-track land reform beneficiaries can successfully engage in agriculture to improve their standard of living. The Vumba and Burma Valley case study is illustrative of how fasttrack land reform was implemented and its socio-economic impact on Zimbabwe's poor and marginalised groups, for instance, female farm workers. The case study offers valuable insights about the survival strategies that ordinary people affected by the land reform exercise are adopting in order to cope with their new circumstances. Data was gathered from a focus group discussion (pilot study), in-depth semi-structured interviews and observation on three farms, as well as interviews with a few government officials, government documents and newspaper reports. The study is useful to countries that are planning or already implementing land reform, for example, South Africa.
Keywords: Land reform -- Zimbabwe; Land use -- Government policy -- Zimbabwe; Land settlement -- Government policy -- Zimbabwe; Farms, Large -- Zimbabwe; Agriculture and state -- Zimbabwe; Agricultural laborers -- Zimbabwe; Zimbabwe -- Economic conditions